P–303 Similar long term recurrence rates with cystectomy and CO2-laser vaporization for endometrioma: a retrospective study. (6th August 2021) - Moura. Tawfic, N; Bafort, C; Meuleman, C; Laenen, A; Va. Schoubroeck, D; Tomassetti, C
Abstract: Study question: Is there a difference in recurrence rate of endometrioma(s) after cystectomy versus CO2-laser vaporization of the cyst wall? Summary answer: Similar rates of imaging based recurrence or need for reintervention for endometrioma were observed after cystectomy versus CO2-laser vaporization. What is known already: Surgical treatment of endometrioma(s) is mainly performed by 2 types of procedures: cystectomy and ablation. When performing surgery for endometrioma(s), a balance should be made between minimal destruction of normal ovarian cortex and maximal completeness to avoid (early) recurrence. Previous studies have shown that cyst recurrence rates were higher with ablation using bipolar current than after cystectomy. However, only 2 groups have evaluated recurrence rates after cystectomy versus CO2 laser vaporization and found no difference with extended follow-up. Furthermore, ablation with CO2 laser may be less invasive than conventional cystectomy with increased preservation of antral follicles in favor of ablation. Study design, size, duration: Single-center retrospective study on data of 271 patients operated between January 2010 and December 2014. Participants/materials, setting, methods: Women of reproductive age (18–45 years), undergoing CO2 laser laparoscopic excision of any rAFS-stage endometriosis with at least one endometrioma, were eligible for the study. All 271 included patients were treated in a tertiary referral center for endometriosis of a University Hospital, and underwent complete CO2-laser laparoscopic surgery for endometrioma(s). 155 underwent cystectomy, 77 CO2 laser vaporization, and 46 a mixed technique. Main results and the role of chance: The mean duration of follow-up was 58 months. Primary outcome studied was the comparison of recurrence rates between cystectomy and vaporization; secondary outcomes included pregnancy rate and ovarian reserve testing. Recurrence was defined as either imaging based (i.e. cyst recurrence identified at ultrasound and/or MRI) or need for reintervention for suspected cyst recurrence. Imaging based recurrence was reported in 9.92% of patients (n = 12/121) treated with cystectomy and in 11.76% of patients (n = 6/51) who underwent a CO2 laser vaporization (p = .62). The need for reintervention for endometrioma(s) was also similar in both groups, with a rate of 3.23% (n = 5/155) after cystectomy and 4.29% (n = 3/70) after CO2 laser vaporization (p = .567). No difference was seen regarding AMH drop pre- versus postoperatively (p=.233). The 2 study groups were similar, except for the mean cyst diameter, which was higher in the cystectomy group (42.36 ± 25.49 mm) compared to the CO2 laser vaporization group (31.7 ± 26.98 mm) (p = <.001). This suggests that smaller endometriomas might be more likely to undergo CO2 laser vaporization. Limitations, reasons for caution: The retrospective character of the study may induce information bias concerning the registration of recurrence. Moreover, regarding the evaluation of imaging-based recurrence, a selection bias cannot be excluded, because most likely only patients complaining about pain would be referred for an ultrasound or planned for a reintervention. Wider implications of the findings: In this study, similar rates of recurrence for endometrioma(s) were observed after cystectomy versus CO2-laser vaporization. Since previous studies suggested that CO2-laser vaporization may cause less damage to the adjacent ovarian tissue, we consider this a valuable alternative technique, especially for women with a future child wish. Trial registration number: S59032